Exploring Pre-Service English Teachers’ Prior Knowledge and Technology Acceptance through AI-Powered Digital Storytelling Training - Ida Isnawati; Fitria Ningsih; Lailatul Nikmah (Wanastra: Jurnal Bahasa dan Sastra, 2026)
There is a concern with the rapid rise of Artificial Intelligence (AI) and the actual readiness of future teachers to use it in their classrooms. Although AI technologies are increasingly discussed in educational contexts, many pre-service teachers still have limited opportunities to gain practical experience in integrating AI-supported tools into classroom teaching. The research-focused report from a larger 2024 research project examines pre-service English teachers’ prior knowledge of AI tools and their perceptions before and after participating in AI-powered digital storytelling training. Using a mixed-methods action research design with a pre–post intervention, the study involved 90 sixth-semester pre-service English teachers enrolled at an Indonesian university. The intervention involved structured training in creating AI-powered digital storytelling materials using tools such as ChatGPT, Canva, and AI Audio Maker. Data were collected using a questionnaire adapted from previous TAM studies that measured key constructs, including Perceived Usefulness, Perceived Ease of Use, Behavioral Intention, Attitude, Trust, and Actual System Use. By comparing mean scores from pre-test and post-test responses, the results show a consistent upward trend in participants’ perceptions of AI tools. The results indicate consistent increases across all TAM constructs, including perceived usefulness (3.79→4.10), perceived ease of use (3.65→3.99), behavioral intention (3.74→4.10), actual system use (3.47→3.95), attitude (3.86→4.03), and trust (3.73→4.14). The findings suggest that hands-on AI-powered digital storytelling projects can effectively enhance pre-service teachers’ confidence and readiness to integrate AI technologies into English language teaching. This study highlights the importance of structured AI training in teacher education programs and provides empirical evidence supporting the integration of AI-assisted digital storytelling as a pedagogical strategy in Indonesian EFL contexts.